Epigenetic histone H3 phosphorylation marks discriminate between univalent- and bivalent-forming chromosomes during canina asymmetrical meiosis - Kalfusová, Radka; Herklotz, Veit; Kumke, Katrin; Houben, Andreas; Kovařík, Aleš; Ritz, Christiane M; Lunerová, Jana (Annals of botany, 2024)
BACKGROUND AND AIMS: Dogroses (Rosa sect. Caninae) are mostly pentaploid, bearing 2n = 5x = 35 chromosomes in somatic cells. They evolved a unique form of asymmetrical meiosis characterized by two types of chromosomes: (1) chromosomes forming bivalents and distributed in the normal sexual way; and (2) chromosomes occurring as univalents and transferred by a female gamete only. In the mature pollen of pentaploid species, seven bivalent-derived chromosomes are transmitted to offspring, and 21 unpaired univalent chromosomes are eliminated during microsporogenesis. To discriminate between bivalent- and univalent-forming chromosomes, we studied histone H3 phosphorylation patterns regulating meiotic chromosome condensation and segregation. METHODS: We analysed histone modification patterns during male canina meiosis in two representative dogrose species, 5x Rosa canina and 5x Rosa rubiginosa, by immunohistochemical and molecular cytogenetics approaches. Immunostaining of meiotic cells included α-tubulin, histone H3 phosphorylation (H3S10p, H3S28p and H3T3p) and methylation (H3K4me3 and H3K27me3) marks. In addition, fluorescent in situ hybridization was carried out with an 18S rDNA probe. KEY RESULTS: In the first meiotic division, univalent chromosomes underwent equational division into chromatids, while homologues in bivalents were segregated as regular dyads. In diakinesis, bivalent chromosomes displayed strong H3 phosphorylation signals in proximal regions, spreading to the rest of the chromosome. In contrast, in univalents, the H3 phosphorylation signals were weaker, occurring mostly outside proximal regions largely overlapping with the H3K4me3 signals. Reduced phosphorylation was associated with relative under-condensation of the univalent chromosomes, particularly at early diakinesis. CONCLUSIONS: We hypothesize that the absence of pairing and/or recombination in univalent chromosomes negatively affects the histone H3 phosphorylation of their chromatin and perhaps the loading of meiotic-specific cohesins. This apparently destabilizes cohesion of sister chromatids, leading to their premature split in the first meiotic division.
Keywords: fosforylace; Phosphorylation; Chromosomes; fluorescence in situ hybridization; histone H3 phosphorylation; dogroses; In Situ Hybridization, Fluorescence; epigeneze genetická; euchromatin and heterochromatin; Epigenesis, Genetic; histony; hybridizace in situ fluorescenční; Meiosis; non-disjunction; 18S ribosomal DNA; canina meiosis; meióza; immunostaining; Rosa genus; Histones; chromozomy